The Role of Reading Corner in Strengthening Students' Character Education at SDN 3 Mrayan Ngrayun Ponorogo - Titin Nur Hasanah; Katni Katni; Riyanto Riyanto (International Journal Labs, 2025)
SDN 3 Mrayan Ngrayun Ponorogo has made innovations in supporting the strengthening of character education through the provision of reading corners in every classroom. This initiative emerged as a response to students' low interest in reading, the lack of fun character learning media, and the need for facilities that are able to instill moral values consistently. The reading corner is not only a place to read, but also a means of character formation through habituation and interaction with reading with positive values. This study aims to identify the role of the reading corner in strengthening students' character education at SDN 3 Mrayan Ngrayun Ponorogo, as well as identify the obstacles and impacts caused. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the reading corner has a strategic role as a means of habituating character values. Through habituation activities in the reading corner, students get used to being independent, choosing readings according to their interests, and obeying the applicable rules. The reading corner also instills an honest attitude and responsibility in caring for books, including reporting if there is damage, and encouraging cooperation through decorating, tidying up, and reading together. However, the implementation of the reading corner still faces obstacles in the form of limited book collections, lack of variety of literacy activities, the absence of special managers, and limited financial support. The impact of the reading corner is real, as can be seen from the habits of students who are more independent in activities in the reading corner without direction, dare to convey the content of the reading, show an honest attitude, and are able to cooperate with friends. This finding confirms that the reading corner is not only a literacy facility, but also an effective medium in strengthening character education through simple and meaningful habituation, so that more comprehensive measurement of effectiveness is needed in the future